Symmetry exploiting control of hybrid mechanical systems - Flasskamp, Kathrin; Hage-Packhäuser, Sebastian; Ober-Blöbaum, Sina (Journal of Computational Dynamics)

High order variational integrators in the optimal control of mechanical systems - Campos, Cédric M.; Ober-Blöbaum, Sina; Trélat, Emmanuel (Discrete & Continuous Dynamical Systems - A)

A gender perspective on business process management competences offered on professional online social networks - Gorbacheva, Elena; Stein, Armin; Schmiedel, Theresa; Müller, Oliver (European Conference on Information Systems)

Potenzialbeurteilung neuer Technologien im Prozesscontrolling - vom Brocke, Jan; Müller, Oliver; Debortoli, Stefan; Reuter, Nadine (Controlling)

Self-Optimizing Organic Cache - Ahmed, Abdullah Fathi

Management and Scheduling of Accelerators for Heterogeneous High-Performance Computing - Beisel, Tobias
The use of heterogeneous computing resources, such as graphics processing units or other specialized co-processors, has become widespread in recent years because of their performance and energy efficiency advantages. Operating system approaches that are limited to optimizing CPU usage are no longer sufficient for the efficient utilization of systems that comprise diverse resource types. Enabling task preemption on these architectures and migration of tasks between different resource types at run-time is not only key to improving the performance and energy consumption but also to enabling automatic scheduling methods for heterogeneous compute nodes. This thesis proposes novel techniques for run-time management of heterogeneous resources and enabling tasks to migrate between diverse hardware. It provides fundamental work towards future operating systems by discussing implications, limitations, and chances of the heterogeneity and introducing solutions for energy- and performance-efficient run-time systems. Scheduling methods to utilize heterogeneous systems by the use of a centralized scheduler are presented that show benefits over existing approaches in varying case studies.

Evolution of Heat Flow Prediction Models for FPGA Devices - Hangmann, Hendrik

Computer Vision basierte Klassifikation von HD EMG Signalen - Haupt, Christian

Microarchitectural optimization by means of reconfigurable and evolvable cache mappings - Ho, Nam; Ahmed, Abdullah Fathi; Kaufmann, Paul; Platzner, Marco (Proc. NASA/ESA Conf. Adaptive Hardware and Systems (AHS))
Keywords: cache storage; field programmable gate arrays; multiprocessing systems; parallel architectures; reconfigurable architectures; FPGA; dynamic reconfiguration; evolvable cache mapping; many-core architecture; memory-to-cache address mapping function; microarchitectural optimization; multicore architecture; nature-inspired optimization; parallelization degrees; processor; reconfigurable cache mapping; reconfigurable computing; Field programmable gate arrays; Software; Tuning

Generator Start-up Sequences Optimization for Network Restoration Using Genetic Algorithm and Simulated Annealing - Kaufmann, Paul; Shen, Cong (Genetic and Evolutionary Computation (GECCO))

Comparison of thread signatures for error detection in hybrid multi-cores - Meisner, Sebastian; Platzner, Marco (Field Programmable Technology (FPT), 2015 International Conference on)

Konzept und Implementation einer Benutzeroberfläche zur Generierung virtueller FPGAs - Meißner, Roland

Acceleration of Artificial Neural Networks on a Zynq Platform - Posewsky, Thorbjörn

Applications of Evolutionary Computation - 18th European Conference, EvoApplications - M. Mora, Antonio; Squillero, Giovanni; Agapitos, Alexandros; Burelli, Paolo; S. Bush, William; Cagnoni, Stefano; Cotta, Carlos; De Falco, Ivanoe; Della Cioppa, Antonio; Divina, Federico; Eiben, A.E.; I. Esparcia-Alcázar, Anna; et al.

Significant papers from the first 25 years of the FPL conference - H.W. Leong, Philip; Amano, Hideharu; Anderson, Jason; Bertels, Koen; M.P. Cardoso, João; Diessel, Oliver; Gogniat, Guy; Hutton, Mike; Lee, JunKyu; Luk, Wayne; Lysaght, Patrick; Platzner, Marco; et al. (Proceedings of the 25th International Conference on Field Programmable Logic and Applications (FPL))

New Codesign Solutions for Modelling and Partitioning of Probabilistic Reconfigurable Embedded Software - Ghribi, Ines; Ben Abdallah, Riadh; Khalgui, Mohamed; Platzner, Marco (Proceedings of the 29th European Simulation and Modelling Conference (ESM))

From Defect Analysis to Gate-Level Fault Modeling of Controllable-Polarity Silicon Nanowires - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; De Micheli, Giovanni (IEEE Transactions on Nanotechnology)

On the design of a fault tolerant ripple-carry adder with controllable-polarity transistors - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; Zhang, Jian; De Micheli, Giovanni; Sanchez, Eduardo; Reorda, Matteo Sonza (2015 IEEE Computer Society Annual Symposium on VLSI)

Fault modeling in controllable polarity silicon nanowire circuits - Ghasemzadeh Mohammadi, Hassan; Gaillardon, Pierre-Emmanuel; De Micheli, Giovanni (Proceedings of the 2015 Design, Automation & Test in Europe Conference & Exhibition)

Over effective hard real-time hardware tasks scheduling and allocation - Guettatfi, Zakarya; Kermia, Omar; Khouas, Abdelhakim (25th International Conference on Field Programmable Logic and Applications (FPL))
Keywords: embedded systems; field programmable gate arrays; operating systems (computers); scheduling; μC/OS-II; FPGAs; OS foundation; SafeRTOS; Xenomai; chip utilization ration; complex time constraints; embedded systems; hard real-time hardware task allocation; hard real-time hardware task scheduling; hardware-software real-time operating systems; partially reconfigurable field-programmable gate arrays; resource constraints; safety-critical RTOS; Field programmable gate arrays; Hardware; Job shop scheduling; Real-time systems; Shape; Software